Comparative Analysis of Immune Responses Induced by Vaccination With SIV Antigens by Recombinant Ad5 Vector or Plasmid DNA in Rhesus Macaques - Hirao, Lauren A (Nature Publishing Group, 2010)
DNA vaccines have undergone important enhancements in their design, formulation, and delivery process. Past literature supports that DNA vaccines are not as immunogenic in nonhuman primates as live vector systems. The most potent recombinant vector system for induction of cellular immune responses in macaques and humans is adenovirus serotype 5 (Ad5), an important benchmark for new vaccine development. Here, we performed a head-to-head evaluation of the Merck Ad5 SIV vaccine and an optimized electroporation (EP) delivered SIV DNA vaccine in macaques. Animals receiving the Ad5 vaccine were immunized three times, whereas the DNA-vaccinated animals were immunized up to four times based on optimized protocols. We observed significant differences in the quantity of IFNγ responses by enzyme-linked immunosorbent spot (ELISpot), greater proliferative capacity of CD8(+) T cells, and increased polyfunctionality of both CD4(+) and CD8(+) T cells in the DNA-vaccinated group. Importantly, Ad5 immunizations failed to boost following the first immunization, whereas DNA responses were continually boosted with all four immunizations demonstrating a major advantage of these improved DNA vaccines. These optimized DNA vaccines induce very different immune phenotypes than traditional Ad5 vaccines, suggesting that they could play an important role in vaccine research and development.